Effects of OROS-MPH Versus Dl-Amphetamine-XR on Driving Performance of ADHD Adolescents - J Gordon Millichap (Pediatric Neurology Briefs, 2006)
Driving performance of 35 adolescent ADHD patients (19 boys/16 girls; mean age 17.8 years) on a driving simulator was compared while taking OROS methylphenidate (Concerta, 72 mg), mixed dl-amphetamine salts (Adderall XR, 30 mg), or placebo in a randomized, double-blind, crossover study at University of Virginia, Charlottesville.